Trade Restriction and Economic Growth: A Study of Developed and Developing Countries - Monadjemi, Mehdi; Lodewijks, John (Archives of Business Research, 2021)
According to the World Bank, most research suggests that unilateral reduction in trade barriers can result in the greatest and the quickest gains in welfare. However, recently United States imposed tariffs on good imported from China and Chinese government retaliated by introducing trade barriers on imports from the United States. Generally, developed counties attempt to improve their trade deficits by allowing the exchange rate to depreciate, whereas developing countries rely more on trade restrictions. In this paper, five developed countries and five developing countries that experienced persistent trade deficits were selected. A VAR statistical technique was used to examine the effects of exchange rate changes of the net trade of two selected groups of countries. It is shown that in case of developed counties, the exchange rate and net trade moved in the same direction. However, the same results were not confirmed for the developing countries.